Mencari, menemukan, dan memoles model petani ramah gambut - Ahmad Muhammad; Nurul Qomar; Sigit Sutikno; Muhammad Yusa; Besri Nasrul; Arifudin Arifudin; Radith Mahatma (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
Friendly peatland utilization is often regarded as ‘difficult’, ‘adding new cost,” and ‘unfavorable’ to the cultivated crops. Such views appear to restrain farmers in general to adopt friendlier methods in utilizing peatlands. In response to the call for improving their practices farmers often demand proven peat-friendly but profittable practices. Therefore, convincing evidences, such as successful farmers with such practices as models, are needed. In one of villages in Siak regency, Riau Province, we encountered a farmer figure that is potentially promoted as a model in this regard. However, after evaluating what he really practiced, we found that some improvements were needed to make his practices truly peat friendlier. Our paper concerns the results of our interactions with this figure in order to improve the: (a) control of groundwater level; (b) prevention of peat decomposition; (c) prevention of peat subsidence; (d) reduction of carbon emission; (e) diversification of the farm’s products; (f) aesthetic value of the farm; and (g) promotion to potential visitors and market the farm’s products.